Effects of microplastics on gut bacteria - Wong, Vivien Yue Teng (2019)
The purpose of this project is to gain insight into the effects of microplastic leachate on the of gut bacteria. Microplastic leachate has become a subject undergoing intense study in the last decade. They may be ingested through the use of plastic products or from the infiltration into the food chain specifically through biomagnification and bioaccumulation. The alarming issue with the presence of microplastics is the fact that microplastic leachate contains both hydrophobic organic contaminants (HOCs) and chemical additives and they are biomagnified to humans who are at the top of the food chain. Multiple research organisations have confirmed the long-term diseases related to ingestion and inhalation of microplastics. Consequently, there are numerous researches carried out providing a platform of information on the effects on marine organisms, especially in the gastrointestinal tract. While there are researches done on the impact of humans, they mostly focus on broader diseases. Far and few have investigated the impact on the human gastrointestinal tract where most microplastics may accumulate. In this project, three common microplastics: Polycarbonate (PC), Polyethylene (PE) and Polypropylene (PP) were used for the preparation of microplastic leachate. After 5-days of leaching, Escherichia coli was dosed into each sample with RCM in aerobic and anaerobic conditions. A 24 hour growth curve was recorded, and a 24 hour morphology was analysed. This was repeated for Clostridium sporogenes under anaerobic conditions. In the analysis, no obvious changes were found in the growth curve and no significant filamentous and membrane damage could be seen. In future studies, plastic leachate could be dosed in gut fluid instead of distilled water to simulate natural conditions.